COMPARISON OF IMMUNOCHROMATOGRAPHIC TEST NEGATIVE HEPATITIS B VIRUS AND HEPATITIS C VIRUS BLOOD DONATIONS WITH ELISA IN PUBLIC AND PRIVATE BLOOD BANKS OF LAHORE - PAKISTAN - Khan, Aftab; Obaid Ullah,; Israr Ahmad,; Ambreen,; Farkhinda Ghafoor, (Journal of Postgraduate Medical Institute, 2023)
Objectives: To determine the frequency of immunochromatographic test for false negative HBV and HCV testing among healthy blood donors in Lahore - Pakistan. Methodology: This was 18 months cross sectional pilot study, conducted in private and public blood banks of city Lahore. After taking formal consent from head of selected Hospital and in charge blood bank/ donors, blood bags screened as HBs Ag and Anti HCV negative by immune-chromatographic (ICT) method, 3-5 ml blood was transferred to coded tube and later transferred to ex-PHRC research Centre NHRC Lahore, where plasma was separated through centrifugation and stored at -40/-20C. Collected samples from this Centre sent to ex-PHRC Research Centre Khyber Medical College Peshawar in cold chain for ELISA testing. Results: Study found that among 385 HBs Ag and anti HCV ICT negative Labeled blood bags 0.8 % was positive for HBs Ag and 2.1% blood bags was positive for anti HCV antibody on ELISA testing. Frequency of AB –ive and A-ive blood bags availability were very rare, 1 % for both types. False negative testing rate of blood bags was comparatively high in public sectors hospitals (1 % for HBs Ag and 3.2% for anti HCV) than private sector hospitals (0.5% for HBs Ag and 1% for anti HCV. False negative ICT testing rate was observed high among blood group B +ive (0.8% for HBV and 4.1% for HCV) than all other blood groups. Conclusion: Study found that 0.8% blood bags were screened falsely negative by immuno-chromatographic method (ICT) for HBs Ag and 2.1% for anti HCV.